Spatial heterogeneity in deployment and upscaling of wind power in Swedish municipalities - Yodefia Rahmad; Fredrik Hedenus; Jessica Jewell; Vadim Vinichenko (Renewable and Sustainable Energy Transition)
Deployment of new onshore wind power faces challenges due to growing resistance, prompting increased interest in the development of effective deployment strategies. One approach is to examine historical deployment to identify factors shaping its distribution within a country. Current literature presents inconsistent results and lacks theoretically grounded approaches. This study enhanced the methodology for analyzing subnational wind deployment in two ways. First, techno-economic, socio-technical, and political perspectives from national energy transition literature were employed to identify relevant deployment mechanisms. Second, the approach differentiated between small-scale and large-scale wind power to avoid conflating results from obsolete technologies. The method is piloted in Sweden where wind deployment varied significantly despite nationwide policies. Findings from Sweden suggest that subnational heterogeneity of wind deployment at the municipality level is not primarily determined by techno-economic factors, but also by socio-technical and political variables. Deployment mechanisms also evolved over time, possibly due to technological upscaling. Small-scale wind power (≤1.5 MW) leveraged agricultural land and accumulated local experience, while large-scale wind power (>1.5 MW) is correlated with political variables such as siting policy and voter turnout. Municipalities with the highest large-scale deployment typically have extensive forest cover, low population density and wind speeds within a lower median range relative to the national median. Findings from Sweden can inform hypotheses for evaluation in other countries and future research can extend the proposed analytical framework to different national contexts.